Decision Support System Application in Selecting The Feasibility of Home Credit Application Using AHP Method - Kamson Sirait; Jonas Franky Rudianto Panggabean (Institute of Computer Science (IOCS), 2020)
Humans in general have a primary need which is none other than a place to live, namely a house. This primary need, not everyone can buy it in cash. Therefore, it is necessary to have a financial body or institution commonly referred to as a bank in order to provide financial assistance in the form of lending, in this case, of course, in the Home Ownership Credit (KPR). In order to simplify and speed up the work process, the right decision making is needed. There are several requirements or criteria in the assessment of prospective customers, this assessment is based on qualitative analysis, namely by looking at the down payment given by the customer, the number of dependents of the prospective customer, the customer's permanent job, the customer's income, the complete documents the customer has fulfilled. Through this research an application has been developed to perform the selection process for prospective customers in order to use an easier method. In this case, the method used by the author is the AHP method. By using the AHP Program method This is expected to determine whether or not a home loan is appropriate for customers